Application of the Principle of Restorative Justice to the Termination of Investigation Warrant (SP3) - Agus Susanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to find out how to apply the principle of restorative justice to the warrant for termination of investigation (SP3). The research method used is a normative legal research method. The legal sources used are from the Legislation and secondary legal materials along with other legal sources.